Strategy of building a wireless mobile communication system in the conditions of electronic counteraction - Serkov, Aleksandr; Kasilov, Oleg; Lazurenko, Bogdan; Pevnev, Volodimir; Trubchaninova, Karyna (National Aerospace University "Kharkiv Aviation Institute", 2023)
The subject of research in this article is the process of building a mobile communication system that operates under electronic countermeasures. The aim is to develop recommendations for building a wireless mobile com-munication system that operates effectively in a complex interfering electromagnetic environment. The strategy for building a mobile wireless communication system is based on the use of a grouping of low-altitude UAVs with ultra-wideband signal technology circulating in control and communication channels, with the integration of artificial intelligence elements into its structure. The objective of this study is to ensure the stable and secure operation of a wireless mobile communication system despite electronic countermeasures. The methods of ana-lytical, temporal positional pulse coding, and fuzzy logical inference were used to make decisions on the transfer of service in the network. The following results were obtained. A strategy for building a wireless mobile com-munication system despite electronic countermeasures has been developed. It is shown that in order to obtain high noise immunity of control and communication channels and to protect information from interception, wire-less ultra-wideband communication technology should be used. This will provide large volumes and speeds of information transmission. A technical solution for the design of an ultra-wideband transceiver antenna system is proposed. Moreover, it is recommended to use the results of data processing in a fuzzy decision-making system for the transfer of service between mobile network nodes in conditions of interference. Conclusions. The scien-tific novelty of the obtained results is as follows. The use of ultra-wideband channels makes it possible to increase the number of control and communication channels in a wireless mobile system almost unlimitedly. The prelim-inary distribution of orthogonal codes between the channels realizes the process of control and communication without the interception of information and mutual interference. The use of the time-position-pulse coding method prevents the occurrence of intercharacter distortions of the encoding ultrashort pulses. This also reduces the level of distortion of information signals caused by multipath propagation, which guarantees the security of information in the system. The use of a fuzzy decision-making system for the transfer of services between mobile network nodes allows dynamically changing the network topology in real time and maintaining high quality of service under electronic countermeasures.

Предметом дослідження в статті є процеси побудови системи мобільного зв’язку, що працює в умовах радіоелектронної протидії. Мета - розробка рекомендацій щодо побудови безпровідної мобільної системи зв’язку, що ефективно працює у складній завадовій електромагнітній обстановці. В основу стратегії побудови системи мобільного безпровідного зв’язку покладено використання угруповання маловисотних БПЛА з застосуванням технології надширокосмугових сигналів, які циркулюють в каналах управління та зв’язку із інтеграцією до її структури елементів прийняття рішення . Завдання дослідження полягає в забезпеченні усталеної та безпечної роботи безпровідної мобільної системи зв’язку в умовах організованої радіоелектронної протидії. В роботі використовувалися методи аналітичного, часового позиційно-імпульсного кодування та нечіткого логічного висновку для прийняття рішень щодо передачі обслуговування у мережі. Отримані наступні результати. Розроблена стратегія побудови безпровідної мобільної системи зв’язку в умовах радіоелектронної протидії. Показано, що для отримання високої завадостійкості каналів управління і зв’язку та захисту інформації від перехоплення слід застосовувати технологію безпровідного надширокосмугового зв’язку, яка дозволяє забезпечити великі обсяги та швидкості передачі інформації. Запропоновано технічне рішення щодо конструкції надширокосмугової приймально-передавальної антенної системи. Причому, рекомендовано використовувати результати обробки даних у нечіткій системі прийняття рішень для передачі обслуговування між вузлами мобільної мережі в умовах завад. Висновки. Наукова новизна отриманих результатів полягає в наступному. Використання каналів із надширокою смугою частот дає можливість практично необмежено збільшити кількість каналів управління та зв’язку у безпровідній мобільній системі. Попередній розподіл між каналами ортогональних кодів реалізує процес управління та зв’язку без перехоплення інформації та взаємних завад. Використання методу часового позиційно-імпульсного кодування запобігає виникненню міжсимвольних спотворень кодуючих надкоротких імпульсів. При цьому також знижується рівень спотворень інформаційних сигналів, які викликані його багатопроменевим розповсюдженням, що гарантує безпеку інформації в системі. Використання нечіткої системи прийняття рішень у випадку передачі обслуговування між вузлами мобільної мережі дає змогу у режимі реального часу динамічно змінювати топологію мережі та підтримати високу якість обслуговування в умовах радіоелектронної протидії.
Стратегія побудови безпровідної мобільної системи зв'язку в умовах радіоелектронної протидії
Keywords: mobile wireless network; security; ultra-wideband control and communication channel; radio-electronic countermeasures; fuzzy system; мобільна бездротова мережа; надширокосмуговий канал управління та зв'язку; радіоелектронна протидія; нечітка система